Mikrorozmnażanie wisienki stepowej (Cerasus fruticosa Pallas) - Szczygieł, Krystyna; Wojda, Tomasz (Leśne Prace Badawcze, 2010)
The aim of this study was to apply the micropropagation method via organogenesis to an endangered species, Cerasus fruticosa Pallas. This species is classified as rare and endangered according to the Polish Plants Red Book. The explants – winter-dormant apical and axillary buds from plants growing in Prof. S. Białobok’s Forest Arboretume in Forest District Syców – were used for culture initiation. Two basal media were applied for adventitious bud and shoot multiplication: WPM and MS supplemented with 0–2 mg•l -1 BAP, 0.1 mg•l -1 IBA, 10–30 g•l -1 sucrose and 200 mg•l -1 both glutamine and casein hydrolysate. The best results of adventitious shoot multiplication were achieved on WPM medium supplemented with 1 mg•l -1 BAP, 0.1 mg•l -1 IBA and 10–20 g•l -1 sucrose. The addition of 5 g•l -1 activated charcoal to WPM medium (without growth regulators) for one month improved adventitious shoot elongation. The half strength MS medium with 2 mg•l -1 of IBA was the most favourable for microshoot rooting. The acclimatized plants survived two winters and flowered. The micropragation applied method makes it possible to preserve ‘clean’ genotypes of this endangered species.